A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.